Manual vibrocompression and nasotracheal suctioning in post-operative period of infants with heart deffects - Assumpção,Maíra Seabra de (2013)
OBJECTIVE: To evaluate the impact of manual vibrocompression and nasotracheal suctioning on heart (hr) and respiratory (rr) rates, peripheral oxygen saturation (SpO2), pain and respiratory distress in infants in the postoperative period of a cardiac surgery. METHODS: Randomized controlled trial, in which the assessments were performed by the same physiotherapist in two moments: before and after the procedure. The infants were randomly divided into two groups: Intervention (IG), with manual chest vibrocompression, nasotracheal suctioning and resting; and Control CG), with 30 minutes of rest. Cardiorespiratory data (SpO2; hr; rr) were monitored and the following scales were used: Neonatal Infant Pain Scale (NIPS), for pain evaluation, and Bulletin of Silverman-Andersen (BSA), for respiratory distress assessment. The data were verified by analysis of variance (ANOVA) for repeated measures, being significant p<0.05. RESULTS: 20 infants with heart disease, ten in each group (seven acyanotic and three cyanotic) were enrolled, with ages ranging from zero to 12 months. In the analysis of the interaction between group and time, there was a significant difference in the variation of SpO2 (p=0.016), without changes in the other variables. Considering the main effect on time, only rr showed a significant difference (p=0.001). As for the group main effect, there were no statistical differences (SpO2 - p=0.77, hr - p=0.14, rr - p=0.17, NIPS - p=0.49 and BSA - p=0.51 ). CONCLUSIONS: The manual vibrocompression and the nasotracheal suctioning applied to infants in postoperative of cardiac surgery did not altered SpO2 and rr, and did not trigger pain and respiratory distress. [Brazilian Registry of Clinical Trials (ReBEC): REQ: 1467].